2005
DOI: 10.1111/j.1467-9361.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Investment in Transportation Infrastructure and Economic Performance in Portugal

Abstract: In this paper, we use a VAR approach to investigate the effects of public investment in transportation infrastructures on private investment, employment, and output in Portugal. Estimation results suggest that public investment crowds in private investment and employment, and has a strong positive effect on output. We estimate that one euro in public investment increases output in the long‐term by 9.5 euros, which corresponds to a rate of return of 15.9%. These figures imply that there are strong long‐term bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 21 publications
7
48
1
1
Order By: Relevance
“…In this respect, the empirical literature can help us to explore different combinations of treated or affected groups based on patterns revealed through previously conducted studies. Consequently, proceeding from the analysis of Pereira and Andraz (2013), who revealed a pattern of negative or insignificant effects of infrastructure provision at the regional level (see also Yoshino and Abidhadjaev [2015]), and positive and significant effects at the aggregate level (Belloc and Vertova 2006;Pereira and Andraz 2005), we address the spillover effects of the railway connection on neighboring regions. Empirical evidence derived from the analysis conducted by Pereira and Andraz (2003) using a vector autoregression approach for transport and communications infrastructure and Pereira and Roca-Sagales (2007) for highways demonstrates positive spillover effects of infrastructure provision on neighboring regions.…”
Section: Assumptions Concerning the Geographical Impact Of Infrastrucmentioning
confidence: 99%
“…In this respect, the empirical literature can help us to explore different combinations of treated or affected groups based on patterns revealed through previously conducted studies. Consequently, proceeding from the analysis of Pereira and Andraz (2013), who revealed a pattern of negative or insignificant effects of infrastructure provision at the regional level (see also Yoshino and Abidhadjaev [2015]), and positive and significant effects at the aggregate level (Belloc and Vertova 2006;Pereira and Andraz 2005), we address the spillover effects of the railway connection on neighboring regions. Empirical evidence derived from the analysis conducted by Pereira and Andraz (2003) using a vector autoregression approach for transport and communications infrastructure and Pereira and Roca-Sagales (2007) for highways demonstrates positive spillover effects of infrastructure provision on neighboring regions.…”
Section: Assumptions Concerning the Geographical Impact Of Infrastrucmentioning
confidence: 99%
“…As well, enhanced transport infrastructure is the essential part for business expansion [70]. Pereira and Andraz [71] estimated for Portugal, in the long-term, that one euro in public investment rises output by 9.5 euros, namely a rate of return of 15.9%. Hu and Liu [72] explored 28 provinces in China from 1985 to 2006 via a spatial econometric model and found that each 1% increase of the transportation investment in China leads to 0.28% increase on GDP.…”
Section: Transport Infrastructure Investments and Economic Growthmentioning
confidence: 99%
“…The fixed-effects approach was selected since the study was limited to a particular group of states [34]. Onward, the nexus between transport infrastructure, associated investments, emissions of carbon dioxide, and economic growth was explored through a panel vector autoregressive model [2,8,39,44,50,55,59,62,64,65,69,71,82,83,87,93,101,105]. Firstly, the unit root of each variable was examined, then the long-run cointegration link among the variables is investigated, and afterwards the panel vector error correction model (henceforth "PVECM") was estimated to infer the Granger causal associations [44].…”
Section: Quantitative Frameworkmentioning
confidence: 99%
“…Finally, and since this is not the first article that deals with infrastructure investment in Portugalindeed we could regard this paper as an update and extension of Pereira and Andraz (2005)-it is important to highlight its contributions to the literature. First, we use a new and recently completed comprehensive data set for infrastructure investment in Portugal from 1978 to 2012 [see Pereira and Pereira (2016)].…”
Section: Introductionmentioning
confidence: 99%